(2m + 3)(m^2 - 2m + 1) =
2m(m^2 - 2m + 1) + 3(m^2 - 2m + 1) =
2m^3 - 4m^2 + 2m + 3m^2 - 6m + 3 =
2m^3 -m^2 - 4m + 3 <===
Answer:x
=
1
,
y
=
−
2
Step-by-step explanation:
What do you need help with?
Answer:
Step-by-step explanation:
we know that
If two figures are similar, then the ratio of its corresponding sides is proportional
Let
x----> the height of cone B
using proportion
Answer:x=0
Step-by-step explanation:
subtract 3 from both sides
3=3=x+3-5x-3
simplify
0=x-5x
switch sides
x-5x
add similar elements ; x-5x=-4x
-4x=0
divided both side by -4
-4x/-4 . = . 0/-4
=0